Consumer Decision-Making Style of Gen Z and Millennials in Choosing Activewear (Study Case: Eiger Act) - Widian, Rifky; Dellyana , Dina (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study explores the decision-making styles and visual preferences of Generation Z and Millennials in purchasing activewear, focusing on Eiger Act, a sub-brand of Eiger Tropical Adventure targeting the Indonesian market. Employing a quantitative descriptive-comparative approach, the research analyzes consumer behavior through the Consumer Style Inventory (CSI) framework and visual preference tests. Findings indicate that both generations share strong orientations toward quality, price/value consciousness, and convenience, with minimal differences in decision-making styles. Gen Z shows greater loyalty to global brands like Nike and Adidas, while Millennials are more flexible and open to local brands. Both groups consistently prefer minimalist and functional designs, favoring simple T-shirts with small logos over complex patterns. These results suggest that Eiger Act should adopt a dual marketing strategy building a strong, trustworthy brand image to appeal to Gen Z and leveraging unique storytelling and product differentiation to attract Millennials. Digital marketing and e-commerce platforms such as Tokopedia and Shopee should be prioritized, alongside the development of minimalist product lines and the use of 3D design technology to accelerate prototyping. This study contributes to consumer behavior literature by providing empirical insights into generational convergence in activewear preferences within emerging markets.